ANALISIS HUBUNGAN USIA DAN PARITAS DENGAN KEJADIAN KETUBAN PECAH DINI: STUDI KASUS KONTROL DI RSUD DR. H. MOHAMAD RABAIN TAHUN 2023 - Misharwati Misharwati; Nia Clarasari Mahalia Putri; Eprilia Eprilia; Asri Noviyanti; Rosyati Pastuty (Jurnal Ilmiah Kebidanan Imelda, 2025)
Premature Rupture of Membranes (PROM) is a significant complication in pregnancy, posing increased risks of morbidity and mortality for both mother and baby. Previous studies have shown varied results regarding the association of maternal age and parity with the incidence of PROM. This study aims to analyze the relationship between age and parity with the occurrence of PROM at Dr. H. Mohamad Rabain Hospital in 2023. A case-control design was employed with a total sample of 352 respondents, divided into case and control groups. The majority of respondents were aged between 20-35 years (76.6%), and most were multiparous (67.6%). Statistical analysis revealed no significant relationship between age and the incidence of PROM (p-value 0.063; OR 0.608; CI 95% 0.372-0.996). However, a significant association was found between parity and the occurrence of KPD (p-value 0.000; OR 0.608; CI 95% 0.372-0.996). The study concludes that age is not a significant factor in the incidence of PROM at Dr. H. Mohamad Rabain Hospital in 2023, while parity shows a significant relationship. Further research is recommended to explore other potential factors influencing the occurrence of PROM.